Efficacy and safety of Piclidenoson in the treatment of plaque psoriasis: a systematic review and meta-analysis of randomized controlled trials - Muhammad Zain Ul Haq (22225279) (2024)
Psoriasis, an autoimmune inflammatory disease characterized by hyperproliferation of keratinocytes, affects 0.2–4.8% of the global population. The disease manifests primarily as plaque psoriasis, causing chronic physical and psychological burdens. Although numerous treatments exist, there is ongoing exploration for novel therapies due to concerns about the toxicity, efficacy, and costs of current options. An A3 adenosine receptor (A3AR) agonist called Piclidenoson has been shown to reduce inflammation and could be used to treat moderate to severe psoriasis. This meta-analysis evaluates the safety and efficacy of Piclidenoson in psoriasis treatment. This meta-analysis was conducted accordance with the PRISMA guidelines and has been registered on PROSPERO (CRD42024566459). A comprehensive search on Cochrane CENTRAL, PubMed/MEDLINE, and Google Scholar was conducted up to July 2024. Included studies were randomized controlled trials (RCTs) involving Piclidenoson. Efficacy outcomes included PASI 75 and PGA 0 or 1, while safety outcomes included adverse events. Pooled outcomes were presented as odds ratio (OR) with 95% confidence intervals (CI). Statistical analysis employed the Mantel-Haenszel random-effects model, and heterogeneity was assessed using the I2 and X2index. Three RCTs with 574 patients (313 Piclidenoson, 261 placebo) met the inclusion criteria. The pooled analysis showed no significant difference in achieving PASI 75 between Piclidenoson and placebo (OR: 1.62, 95% CI 0.70–3.75, P= 0.26, I2 = 12%). However, Piclidenoson significantly improved PGA scores (OR: 2.74, 95% CI 1.22–6.16, P= 0.01, I²=0%). Safety assessment revealed no significant differences in adverse events, including nervous system, gastrointestinal, musculoskeletal, renal, and infections, compared to placebo. Piclidenoson demonstrates a significant improvement in PGA scores and a favorable safety profile, suggesting it could be a valuable addition to plaque-like psoriasis treatment. Further research with larger, longer-term RCTs is needed to confirm its efficacy and optimize clinical use. Other Information Published in: Archives of Dermatological Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00403-024-03506-y